IMPLEMENTASI HUKUM WARIS ISLAM DI INDONESIA PRESPEKTIF KAJIAN NORMATIF DAN REALITAS SOSIAL - Dwi Dasa Suryantoro Dwi (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2025)
Islamic inheritance law is a branch of law that regulates the distribution of a person's inheritance based on sharia provisions. In the Indonesian context, although Islamic inheritance law has been regulated normatively in Law No. 3 of 2006 concerning Religious Courts, its implementation is often hampered by social, cultural factors, and varying interpretations. This article aims to analyze the basic principles of Islamic inheritance law, the dynamics of its application in Indonesia, and the challenges and solutions in implementing Islamic inheritance law in Indonesian society. This study uses a descriptive-qualitative method, with a normative and empirical approach. The results of the study indicate that although Islamic inheritance law has been recognized in the Indonesian legal system, there is a disharmony between legal provisions and social practices that occur in the field.